2020
DOI: 10.1038/s41416-020-01117-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide analysis reveals functional modulators of drug sensitivity and post-treatment survival in chronic lymphocytic leukaemia

Abstract: BACKGROUND: Chronic lymphocytic leukaemia (CLL) patients display a highly variable clinical course, with progressive acquisition of drug resistance. We sought to identify aberrant epigenetic traits that are enriched following exposure to treatment that could impact patient response to therapy. METHODS: Epigenome-wide analysis of DNA methylation was performed for 20 patients at two time-points during treatment. The prognostic significance of differentially methylated regions (DMRs) was assessed in independent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The transcript of SLCO3A1 was also observed to be increased following treatment with 5-Aza-dC. 38 NTRK3 methylation silenced NTRK3 expression which induced neoplastic transformation in vitro and tumor growth in vivo; reconstitution of NTRK3 induced apoptosis in colorectal cancers. 43 DNA methylation profiling analysis and validation experiments showed that NAV1 was significantly hypomethylated in breast cancers; 44 while overexpression of members of the neuron navigator gene family was reported to promote invasion and predict poor prognosis.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The transcript of SLCO3A1 was also observed to be increased following treatment with 5-Aza-dC. 38 NTRK3 methylation silenced NTRK3 expression which induced neoplastic transformation in vitro and tumor growth in vivo; reconstitution of NTRK3 induced apoptosis in colorectal cancers. 43 DNA methylation profiling analysis and validation experiments showed that NAV1 was significantly hypomethylated in breast cancers; 44 while overexpression of members of the neuron navigator gene family was reported to promote invasion and predict poor prognosis.…”
Section: Discussionmentioning
confidence: 91%
“… 37 Higher methylation level of SLCO3A1 (also known as OATP3A1) was associated with shorter post-treatment survival of patients with chronic lymphocytic leukaemia. 38 Univariate Cox regression and Kaplan–Meier survival analyses showed that high methylation located in NTRK3 gene was significantly associated with poor prognosis in patients with esophageal squamous cell carcinoma (HR = 1.79). 39 In agreement with these studies, we also found that patients with a high methylation level of MEG3 (HR = 1.18), SLCO3A1 (HR = 5.852) and NTRK3 (HR = 4.930) were at a higher risk of having unfavorable RFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we have previously determined that exposure to chemotherapy leads to increased levels of DNA methylation at the HOXA4 locus in remission samples from both adult and childhood ALL [ 15 ], a finding that was replicated here. In addition, we have demonstrated that treatment of chronic lymphocytic leukaemia patients, results in selection for altered methylation of a number of genes, including hypermethylation of HOXA4 , in the leukaemia cells [ 32 ]. Restoration of HOXA4 expression re-sensitises CLL cells to multiple therapeutic agents, identifying a direct role for HOXA4 in control of sensitivity to chemotherapeutic agents with different mechanisms of action [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some genomic mutations have been found in HCC, more genes with aberrant expression accumulate in HCC (7)(8)(9). Epigenetic modulation is one of the critical mechanisms contributing to the dysregulated expression of genes (10)(11)(12). As one of the epigenetic modulation manners, histone methylation modification exerts multiple effects on gene transcription (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%